(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores imagination as a reflective faculty integral to philosophical thought and introduces an algorithmic model of semiogenesis—the generation of meaning through signs. It analyzes how human identity forms through reflective thinking and self-negation, drawing on the ideas of Descartes, Kant, Sartre, Heidegger, Saussure, Derrida, and Deleuze. The text argues that concepts and meanings emerge relationally via oppositions and negations, which are not ontological givens but cognitive and linguistic constructions. It proposes a model wherein philosophical concepts undergo ontological negation to produce new, logically coherent but non-real alternatives, fostering conceptual creativity and knowledge evolution. The essay also contrasts human consciousness’s openness to “not-knowing” and self-transformation with artificial intelligence’s closed, fixed operations, emphasizing consciousness’s paradoxical nature of continuous self-negation without dissolution. This framework offers insights for philosophy, semiotics, and the development of AI cognition algorithms.